2019
DOI: 10.1002/er.4507
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performance of air conditioning systems by using phase change materials: A review

Abstract: Summary This paper reviews the application of phase change materials (PCMs) for improving the performance of air conditioning systems. The different methods of integrating PCMs into air conditioning systems are presented. Moreover, the effects of PCM geometry, flow, and heat transfer characteristics on the performance of air conditioning systems and the potential use of PCMs in increasing the energy savings and coefficient of performance of air conditioning systems are also discussed. Recent studies on the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 96 publications
0
22
0
Order By: Relevance
“…They are mainly involved in storing the heat energy. Phase change materials (PCMs) are used in concentrated power plants, solar water heating, solar air heaters, hybrid electric vehicles, electronic cooling, solar thermal cooling, and air conditioning applications . PCMs are not directly used to store electrical energy or with the grid due to thermal energy storage.…”
Section: Significance Of Esss Used With Ressmentioning
confidence: 99%
“…They are mainly involved in storing the heat energy. Phase change materials (PCMs) are used in concentrated power plants, solar water heating, solar air heaters, hybrid electric vehicles, electronic cooling, solar thermal cooling, and air conditioning applications . PCMs are not directly used to store electrical energy or with the grid due to thermal energy storage.…”
Section: Significance Of Esss Used With Ressmentioning
confidence: 99%
“…Omara et al presented a review on the different methods of using phase change materials (PCMs) for improving the performance of air conditioning systems. Wang et al proposed a heat pipe air conditioning (AC) system using heat pipe heat exchanger (HPHE) to realize secondary heat recovery.…”
Section: Introductionmentioning
confidence: 99%
“…7 Research and development of integration of solar air heater with thermal energy storage material have become the main focus in the field of solar engineering technology. 10,11 A review study of thermal energy storage integration with solar heaters has been conducted by Haldorai et al 12 From the study, it is concluded that solar heaters with latent heat energy storage material as a thermal energy storage component provide a better thermal efficiency when compared with solar heaters employing other types of thermal energy storage materials. The method of latent heat with the application of phase change material (PCM) has received a special attention because of its higher energy storage density compared with sensible heat energy storage material.…”
Section: Introductionmentioning
confidence: 99%
“…Methods of storing thermal energy including sensible heat and latent heat have been employed. Many solar air heater applications using latent heat energy storage materials such as hydrated salt, 13 palmitic and lauric acid, 14,15 and technical grade paraffin wax 11,12 have been studied. 8,9 It works on the principle where the material itself will store and release an amount of heat when the phase changes during the operation.…”
Section: Introductionmentioning
confidence: 99%